Pendidikan Gizi di UPT SDN 060831 Medan dan Pengaruhnya terhadap Perubahan Pengetahuan, Perilaku, dan Sikap - Christo Christo; Annisa Febriana (STIKES Columbia Asia Medan, 2024)
School-aged children who engage in improper eating behaviors may face serious nutritional problems. During this crucial growth stage, meeting their nutritional needs must be closely monitored. A lack of knowledge about nutritional education can lead children to choose unhealthy foods. Healthy foods are those that contain balanced nutrition. The influx of fast food into Indonesia's food sector can also influence the eating habits of the population. To prevent future nutritional issues, it is important to provide nutritional education to elementary school children to enhance their knowledge, attitudes, and practices in choosing healthy foods and snacks. The food menu for school-aged children should contain balanced nutrition to meet the body's needs. This study aims to examine the impact of nutritional education on the knowledge of fifth-grade students at UPT SDN 060831 Medan regarding the consumption of healthy and nutritious foods. The study involved 64 respondents divided into two groups: those who received nutritional education and those who did not. The respondents were fifth-grade students aged 10–13 years. Data were collected through questionnaires. A pre-test was initially conducted on both groups. Then, the education group received four sessions of nutritional education. Two months later, final data were obtained through a post-test. The results of the study indicated that providing nutritional education had an impact on the knowledge, attitudes, and food consumption behaviors of fifth-grade students at UPT SDN 060831 Medan.